Islamic Rulings and Financial Technology (Fintech): An Analysis on the Relevance and Implications - Hakim, Rahmad; Irawan, Mohammad Deny (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2019)
Industrial Revolution 4.0 has produced rapid technological developments to support the ease of human activity in all lines of life. In the economic and financial fields, this development is known as financial technology, commonly known as Fintech. Like two sides of a coin, financial technology offers ease of service in transactions, time efficiency, transaction flexibility, to increase financial literacy and information technology for the public. Conversely, some of the negative impacts of this financial technology include, the increasing culture of consumerism, hedonism to the practice of new style moneylenders that determine high-interest rates for borrowers online, as well as ways of billing outside the fair range. This study aims to conduct an in-depth analysis related to the role of Islamic rulings in the development of financial technology. The conclusions of this study are some of the roles of Islamic rulings in developing financial technology divided into three key aspects; first, as a preventive mechanism to avoid fraud transactions. Second, as a moral guide (ethical guidelines) to maintain that all transactions prioritize the principles of honesty and compliance with sharia principles. Third, as a means of socializing Islamic rulings (muamalah fiqh), especially in transactions that use financial technology instruments. Revolusi Industri 4.0 menghasilkan perkembangan teknologi yang begitu pesat guna menunjang kemudahan aktivitas manusia dalam segala lini kehidupan. Dalam bidang ekonomi dan keuangan, perkembangan ini dikenal dengan tekonologi finansial atau biasa dikenal dengan FinTech (financial technology). Ibarat dua sisi mata uang, teknologi finansial menawarkan kemudahan layanan dalam transaksi, efisensi waktu, fleksibilitas transaksi, hingga peningkatan literasi keuangan dan teknologi informasi bagi masyarakat. Sebaliknya, beberapa dampak negatif dari teknologi finansial ini diantaranya adalah, meningkatnya budaya konsumerisme, hedonisme hingga praktik rentenir gaya baru yang menentukan bunga yang tinggi bagi para peminjam dana secara online, serta cara penagihan di luar batas kewajaran. Penelitian ini bertujuan untuk melakukan analisis secara mendalam terkait peran kaidah fikih dalam pengembangan financial technology. Kesimpulan dari penelitian ini adalah beberapa peran kaidah fikih dalam pengembangan financial technology terbagi menjadi tiga, yaitu: pertama, sebagai mekanisme preventif untuk menghindari kecurangan transaksi. Kedua, sebagai petunjuk moral (ethical guideliness) agar segala transaksi mengutamakan asas kejujuran dan kepatuhan terhadap prinsip-prinsip syariah. Ketiga, sebagai sarana sosialisasi fikih muamalah, khususnya dalam transaksi yang menggunakan instrumen financial technology.